One rough man [large type] - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2011)
They call it the Taskforce. Their existence is as essential as it is illegal. Commissioned at the highest level of the U.S. government, protected from the prying eyes of Congress and the media. Built around the top operators from across the clandestine, intelligence, and special forces landscape and designed to operate outside the bounds of U.S. law. Pike Logan was the most successful operator on the Taskforce, his instincts and talents unrivaled-until personal tragedy permanently altered his outlook on the world. Pike knows what the rest of the country might not want to admit: The real threat isn't from any nation, any government, any terrorist group. The real threat is one or two men, controlled by ideology, operating independently, in possession of a powerful weapon.